Prognostic significance of β2-microglobulin decline index in multiple myeloma - Zhang, Tianyu; Lin, Zhili; Zheng, Ziwei; Wang, Quanqiang; Zhou, Shujuan; Zhang, Bingxin; Zheng, Dong; Chen, Zixing; Zheng, Sisi; Zhang, Yu; Lin, Xuanru; Dong, Rujiao; et al. (Frontiers in Oncology, 2024)
We aimed to assess the prognostic significance of β2-microglobulin decline index (β2M DI) in multiple myeloma (MM). 150 MM patients diagnosed with MM were enrolled in this study. Cox proportional hazards model was used to analyze the uni-and multivariate prognosis in training cohort(n=105). β2M DI showed significant correlation with prognosis in both uni-and multivariate analyses and had a good correlation with complete response (CR) rate and deep remission rate. A new combined prognostic model containing β2M DI was built up based on the data in training cohort. The ROC and calibration curves in validation cohort(n=45) indicated a good predictive performance of the new model. Based on the median risk score of the training group, we classified patients into high-and low-risk groups. In both training and validation groups, patients in the low-risk group had 2 longer overall survival (OS) time than that in the high-risk group(p<0.05). In conclusion, β2M DI is a good predictive index for predicting treatment response and survival time in MM patients. The prognostic model added with β2M DI showed a better correlation with OS.